A DREB-Like Transcription Factor From Maize (Zea mays), ZmDREB4.1, Plays a Negative Role in Plant Growth and Development - Li, Shixue; Zhao, Qian; Zhu, Dengyun; Yu, Jingjuan (Frontiers in Plant Science, 2018)
The DREB (dehydration-responsive element binding)-type transcription factors are classified into 6 subgroups, named A-1 to A-6. The members of DREB A-1 and A-2 subgroups have been reported to be involved in response to various abiotic stresses. However, there were only a few genes belonging to A-3 to A-6 subgroups to be reported. In this study, we cloned a DREB A-4 subgroup gene from maize (Zea mays), ZmDREB4.1, and analyzed its characteristics and functions. ZmDREB4.1 was expressed in roots, stems and leaves at very low levels. It was not induced by any biotic or abiotic treatment. ZmDREB4.1 was located in the nucleus, could directly bind to the DRE element and functioned as a transcriptional activator. The constitutive expression of ZmDREB4.1 in tobacco (Nicotiana tabacum L.) repressed leaf extension and hypocotyl, petiole and stem elongation. In maize, overexpression of ZmDREB4.1 repressed calli growth and regeneration. Further analysis showed that the smaller leaves of transgenic tobacco resulted from inhibition of cell division. The contents of cytokinin and auxin in transgenic leaves were severely decreased. The shorter hypocotyls, stems and petioles of transgenic tobacco were caused by inhibition of cell elongation. The transgenic hypocotyls, stems and petioles contained reduced gibberellin levels. Application of exogenous GA3 rescued the shorter hypocotyls, stems and petioles, but not the smaller leaves. These results demonstrated that ZmDREB4.1 plays an important role in the negative regulation of plant growth and development.